Spatiotemporal differentiation and trade-off/synergy relationships of ecosystem service values in a national park pilot area in China - Peng Wang; Le Li; Zhiqiang Gao; Nan Li; Dongyang Han (Humanities & Social Sciences Communications)
Abstract The scientific evaluation of the ecosystem service value (ESV) of national parks and understanding the trade-offs and synergies between different ecosystem services (ESs) are crucial for advancing the establishment of China’s national park system. However, current research on ESs in national parks is mostly focused on the value assessment of certain types of services. The analysis of their impacts under specific socioeconomic conditions remains very limited, and research on the trade-offs and synergies between different ESs is scant. This study focuses on China’s Qianjiangyuan National Park (QNP) pilot area. To evaluate its ESV at both the temporal and spatial scales, models and tools including value equivalent factors, partial least squares regression, sensitivity analysis, spatial autocorrelation, and trade-off/synergy assessment are utilized. Moreover, the influencing factors of ESV evolution under specific socioeconomic conditions are analyzed, and the trade-off/synergy relationships between ESVs are identified. The results indicate the following. (1) The total ESVs in 1990, 2000, 2010, 2015, and 2020 were respectively CNY 170.63 × 107, 169.65 × 107, 171.89 × 107, 171.95 × 107, and 172.11 × 107. Forest land was the main contributor to ESV, and the type of ES with the highest contribution rate was regulating services. (2) Positive spatial autocorrelations were found for ESVs in the national park pilot area, indicating a clustered distribution pattern. High-value clusters were identified in Suzhuang Town and Qixi Town. (3) The added value of secondary industries, the added value of primary industries, and the added value of agriculture, forestry, animal husbandry, and fishery were found to be the most important factors affecting ESV changes in the pilot area. The tea yield had no effect on the evolution of ESV. (4) In the pilot area, synergies between ESs were more stable than trade-offs, with synergies accounting for 66.67%. Trade-offs primarily existed between food production services and other services. Compared with previous investigations, this research represents a long-term, multi-scale, and comprehensive dynamic study on the only national park system pilot area in eastern China. Moreover, it presents a set of socioeconomic evaluation indicators suitable for creating national parks in economically developed, densely populated areas with complex land ownership complex. The research results enhance the comparability, generalizability, and replicability of national park ESV evaluation methods and outcomes, and provide a valuable reference for conducting ES research in other types of nature reserves.